THE CCB TREATMENT OF SIXTEEN INDONESIAN WOOD SPECIES AGAINST MARINE BORERS - Mohammad Muslich (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2006)
This study was conducted to provide basic information on the treatment of some wood species using a copper bichromated boron (CCB). The specimens were treated with CCB for 2 hours in a 150 psi of full cell process. The treated and untreated wood samples were tested against marine borers for 4, 8 and 12 months. The results indicated that full cell process with CCB were able to prevent marine borers attack. Untreated wood specimens were susceptible to marine borers attack, except Iara (Metrosiderospetiolata Kds.) and kandole (Diploknema oligomera HJ.L.). The attacking borers are Martesia striata Linn of the Pholadidae family, Teredo bartschi Clapp., Dicyathifer manni Wright and Bankia cieba Clench. of the Teredinidae family. However, crustaceans were found clinging to the wood specimens when they were taken from the sea. These crustaceans belongs to Sphaeromatidae family.